Performan Reproduksi Induk Sapi Crossbreed (Bos Javanicus X Bos Taurus) di Wilayah Kecamatan Kupang Timur - Matheus Dede; Tarsisius C Tophianong; Nancy D.F.K Foeh (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Crossbreed cattle is the result of crosses between different breeds of cattle with the aim of increasing the genetic quality of local cattle. The advantages of crossbreed cattle include good production performance, high selling price and greater body weight compared to local cattle. The purpose of this study was to determine the reproductive performance of crossbreed cows (bos javanicus x bos taurus) in the district of East Kupang covering estrus cycle, days open, service per conception, conception rate, pregnancy rate, calving rate, and calving interval. The number of cows used in this study were 75 crossbreed cows (bos javanicus X bos taurus) from smallholder farms aged 4-7 years. The method used is observational through interviews with farmers and rectal examination to determine the reproductive status of livestock. The analysis used is descriptive analysis. The results obtained showed that the average estrus cycle was 28.6 days, days open 151 days, service per conception was 3.9, conception rate was 58.6%, pregnancy rate was 65.45%, calving rate was 34.6%, and calving intervals of 14.29 months. The results of this study illustrate that there has been a decline in the reproductive performance of crossbreed cattle (bos javanicus X bos taurus) in the Kupang Timur sub-district, Kupang district, so it is necessary to improve reproductive management.